1995
DOI: 10.1002/dvg.1020160302
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative feedback loops affect the transcription of IME1, a positive regulator of meiosis in Saccharomyces cerevisiae

Abstract: The IME1 gene of Saccharomyces cerevisiae encodes a transcription factor that is required for the expression of meiosis-specific genes. Like many of the genes it regulates, IME1 itself is expressed according to the following complex pattern: barely detectable levels during vegetative growth, and high induced levels under starvation conditions, followed by a subsequent decline in the course of meiosis. This report examines the influence of Ime1 protein on its own expression, demonstrating feedback regulation. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Expression of Ime2p leads to the eventual repression of IME1 transcription during late stages of meiosis (Shefer-Vaida et al, 1995;Smith and Mitchell, 1989). More directly, Ime2p kinase may phosphorylate Ime1p and target it for degradation (Guttmann-Raviv et al, 2002).…”
Section: Ime2 Repression Of Ime1mentioning
confidence: 99%
“…Expression of Ime2p leads to the eventual repression of IME1 transcription during late stages of meiosis (Shefer-Vaida et al, 1995;Smith and Mitchell, 1989). More directly, Ime2p kinase may phosphorylate Ime1p and target it for degradation (Guttmann-Raviv et al, 2002).…”
Section: Ime2 Repression Of Ime1mentioning
confidence: 99%
“…Under meiotic conditions, i.e., nitrogen depletion and the presence of a nonfermentable carbon source such as acetate, transcription of IME1 is induced transiently in MATa/ MAT␣ diploids (22). It is not known whether this transient transcription reflects transient availability of the Ime1 protein.In addition, the IME1 promoter is subject to positive autoregulation (40,43,44), as well as negative-feedback regulation by both Ime1 and Ime2 (43,48,49).Another important regulator of meiosis and sporulation is the serine/threonine protein kinase Ime2 (12,24,34,48,49). Diploid cells with deletions of IME2 show a 5-to 12-h delay in the transcription of early meiosis-specific genes, a reduction in their level of expression, and extremely low RNA levels of middle and late genes (34,49).…”
mentioning
confidence: 99%
“…The Ime2 protein abundance in rich medium is 538 molecules per cell (Lu et al, 2006), and this number is assumed as the basal level of each proteins in our model (10-11nM). As the maximum Ime1 protein expression level is around relative levels of 6 and 7 (ȕ-gal units: 60 and 70) in (SheferǦVaida et al, 1995), the maximum protein level is then approximately 100nM. Considering the maximum Ime1 protein expression relative level of 6 (SheferǦVaida et al, 1995), and as the experiments revealed that Rpd3/Sin3 is at its maximum activity at early stage (Pnueli et al, 2004;Rubinstein et al, 2007), initial condition for Rpd3/Sin3 is decided as 60nM (6 times from the basal level).…”
Section: Typical Meiosis Initiation Conditions Include Low Basal Levementioning
confidence: 95%
“…(Ray et al, 2013) (Rubinstein et al, 2007)). Further, the model is not validated with the available experimental data of the temporal behaviour of the Ime1 and Ime2 protein expressions (Nachman et al, 2007;SheferǦVaida et al, 1995).…”
Section: Introductionmentioning
confidence: 95%